Türk hukukunda taksir - Topaç, Tahir Hami (My University, 2011)
Bir şey yapabilirken çekinip yapmama, kusur etme anlamlarına gelen ve Arapça kökenli bir kelime olan taksir, 5237 sayılı TCK’nın 22/ 2 madde ve fıkrasında “dikkat ve özen yükümlülüğüne aykırılık dolayısıyla, bir davranışın suçun kanuni tanımında belirtilen neticesinin öngörülmeyerek gerçekleştirilmesidir.” şeklinde tanımlanmış ve 22/ 1 madde ve fıkrasınca taksirle işlenen fiillerin yalnızca kanunda açıkça gösterildiği hallerde cezalandırılacağı belirtilmiştir. 5237 sayılı TCK’nın 22/ 3 madde ve fıkrasında ise bilinçli taksire yer verilmiş ve “kişinin öngördüğü neticeyi istememesine karşın, neticenin meydana gelmesi” şeklinde tanımlanmıştır. Gerek doktrin gerekse uygulamada taksirin unsurları; taksirin cezalandırılacağı hususunda kanunda hüküm bulunması, dikkat ve özen yükümlülüğünün yerine getirilmemiş olması, hareketin iradi olması, neticenin öngörülebilir olması, neticenin istenmemiş olması ve hareket ile netice arasında nedensellik bağının bulunmasıdır. Taksirin oluşması için sayılan bu unsurlarının hepsinin bulunması gerekir. 765 sayılı TCK’da taksirin derecelendirilmesi yöntemi yokken 16.07.1964 tarihli ve 501 sayılı yasa ile adı geçen yasanın 455 ve 459.maddelerinde değişiklik yapılmış, taksirle yaralama ve taksirle öldürme suçlarında kusurun 1/ 8’den 7/ 8’e kadar derecelendirilerek cezanın kusur oranında indirileceği kabul edilmiştir.5237 sayılı TCK döneminde ise kusur oranında cezadan indirim yapılması uygulamasına son verilmiş ve adı geçen yasanın 22/ 4 madde ve fıkrasınca taksirle işlenen suçtan dolayı verilecek cezanın failin kusuruna göre belirleneceği hükme bağlanmıştır. Yine yasanın 61/ 1-f madde, fıkra ve bendine göre ceza belirlenirken hâkim somut olayda failin taksire dayalı kusurunun ağırlığını gözetmek zorundadır. 5237 sayılı TCK’nın 22/ 6 madde ve fıkrasına göre taksirli hareket sonucu neden olunan netice, münhasıran failin kişisel ve ailevi durumu bakımından, artık bir cezanın hükmedilmesini gereksiz kılacak derecede mağdur olmasına yol açmışsa ceza verilmez; bilinçli taksir hâlinde verilecek ceza yarıdan altıda bire kadar indirilebilir. Manevi Unsur, Taksir, Bilinçli Taksir, Öngörebilme, Kusur

As a borrowed word from Arabic, “negligence” means, literally, acting wrongfully whereas one could do otherwise, and is defined in law as, according to Article and Section 22/ 2 of the Turkish Penal Code No. 5237, “against the obligation of having due attention and care, realizing a wrongful action in such a way that the outcome of that action as defined in law has not been anticipated”, and therefore, it has been stated that negligence actions can be penalized only in circumstances as defined clearly in law according to Article and Section 22/ 2. On the other hand, in Article and Section 22/ 3 of the Turkish Penal Code No. 5237 deliberate negligence is also recognized and defined as “the realization of an outcome although one has not intended such an anticipated outcome”. Both in law and in practice, the elements of negligence are; that there is a provision in the code that a negligence will be penalized, that the obligation of having due attention and care is not fulfilled, that the action is realized deliberately, that the outcome of the action can be anticipated, that the action is not intended, and that there is a causal link between the action and outcome. For negligence to take place, all these elements of negligence should exist. Whereas in the Turkish Penal Code No. 765, there is no mentioning of gradation of a tort, with the Code No. 501 introduced on 16.07.1964, Articles 455 and 459 of the said Code are amended such that it has thus recognized that, in cases of injuries and murders due to negligence, the said tort to be graded from 1/ 8 to 7/ 8 and the penalty to be accommodated by a reduction commensurate with the assessed grade. On the other hand, during the command of the Turkish Penal Code No. 5237, the implementation of reduction of penalty commensurate with the assessed grade has been dispensed with, and, in compliance with Article and Section 22/ 4 of the said Code, it has been stipulated that the penalty to be given due to a negligence crimes should be determined according to the tort of the owner of the action. By the same token, in compliance with Article, Section and Subsection 61/ 1-f, for the determination of the penalty, a judge must consider, in a concrete case, the weight of the negligence tort as realized by the owner of the action. According to the Article and Section 22/ 6 of the Turkish Penal Code No. 5237, if the outcome due to some negligence action has caused, from both a personal and his or her family perspective, some grievance of such an extent that further penalty given to him or her would be unnecessary, then, such a penalty is avoided; in the case of deliberate negligence, the penalty can be reduced by a ratio from one half down to one sixth. Moral Element, Negligence, Deliberate Negligence, Anticipatio, Tort
Keywords: Bilinçli Taksir; Hukuk; Kamu Hukuku; Manevi Unsur; Suçlar_Hukuk; Türk Ceza Kanunu